(untitled) (Signifiances (Signifying), 2022)
This paper intends to model the individual conditions of mutual understanding from a semantic point of view. I first show that the standard explanation based on an alleged close homology of linguistic competences within a community comes up against the very high semantic variability between individuals, as regards lexical availability and semantic composition of signs, which results from their geo-, socio-, plurilectal differences, or from differences in their discursive memories or their own histories. I then explain how a mediationist theory escapes these difficulties by emphasizing the interdependence of language and cognition and by bringing to light the individual dynamics involved in semantic competences. I finally set out a typology of meaning contents, which takes account of the fact that meanings are polyphonically structured at the individual level. On this basis I reexamine what ‘to share a language’ actually means.